Innovative hybrid nanostructures: pioneering advances in modern therapy - Harun-Ur-Rashid, Mohammad; Jahan, Israt (Frontiers in Nanotechnology, 2024)
Innovative hybrid nanostructures have revolutionized modern therapy by combining different materials at the nanoscale, offering unique synergistic properties that enhance their functionality.These advancements are pivotal in areas such as targeted drug delivery, photothermal and photodynamic therapy, and gene delivery, where they significantly improve therapeutic outcomes.The article discusses the synthesis methods and characterization techniques of HNSs, providing a comprehensive analysis of their mechanisms of action in various therapeutic applications.Highlighted case studies demonstrate their efficacy in treating conditions such as cancer, neurodegenerative diseases, and cardiovascular disorders, underscoring their potential to bridge existing gaps in medical treatments. The review also emphasizes the need for continued innovation and interdisciplinary collaboration to optimize these nanostructures for clinical applications.Future research should focus on enhancing biocompatibility, targeting capabilities, and integrating advanced imaging techniques and AI-driven applications to further improve the precision and efficacy of HNSs in therapy. These advancements herald a new era in medical treatment, offering transformative solutions for complex diseases.